2002
DOI: 10.1007/s11606-002-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation in a homeless population

Abstract: This cross-sectional study sought to determine the prevalence of smoking, readiness to quit, and preferences for smoking cessation treatments among a sample of 236 homeless adults attending 9 sites serving homeless persons (mean age 41.8 years; 73% male). Two thirds (69%) were current smokers, of whom 37% reported readiness to quit smoking within the next 6 months. In bivariate analyses, persons were significantly (P <.05) more likely to be ready to quit if they had tried to quit in the past and if they had so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…HIV-infection, unstable housing, and substance use disorders) (2, 3, 20, 47-49), we found that the majority of the participants were interested in quitting smoking. While motivation to quit smoking was associated with making a quit attempt, less than one-quarter made a quit attempt during the two-year study interval.…”
Section: Discussionmentioning
confidence: 83%
“…HIV-infection, unstable housing, and substance use disorders) (2, 3, 20, 47-49), we found that the majority of the participants were interested in quitting smoking. While motivation to quit smoking was associated with making a quit attempt, less than one-quarter made a quit attempt during the two-year study interval.…”
Section: Discussionmentioning
confidence: 83%
“…Other reasons may involve health-care provider behaviors and attitudes toward tobacco use among homeless persons, perpetuating erroneous assumptions that homeless smokers lack interest in smoking cessation. 89 However, contrary to myths that homeless individuals lack interest in smoking cessation, recent studies demonstrate that when provided opportunities to do so, homeless smokers will enroll in smoking cessation programs as well as exhibit high levels of motivation to quit smoking. 10 For example, in a recent survey of 350 homeless adults aged 50 or older, smoking quit attempt rates were similar to the general population; although, successful quitting was lower.…”
Section: Introductionmentioning
confidence: 99%
“…23 Among homeless Veterans, the rate of smoking remains alarmingly high and nearly triple than that of the US general population (21%), with estimates ranging between 70 to 80%. 45 Indeed, homeless Veterans are overrepresented among tobacco-using individuals within community health settings and they are disproportionately represented within the tobacco-using homeless population, 6 rendering this population particularly vulnerable to smoking-related morbidity and mortality. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, smoking-attributable deaths are disproportionately high among the homeless (4, 9), even when health insurance coverage for the treatment of chronic smoking-related diseases is provided (7). However, studies suggest that anywhere between a third to three-quarters of homeless smokers are interested in quitting smoking (6, 10, 12, 13) and are receptive to getting assistance from healthcare professionals to do so (10). Unfortunately, lifetime quit rates among the homeless are very low (~9%)(1), with data from one study suggesting that the majority of homeless smokers who try to quit, even during an aided quit attempt, are unable to maintain abstinence for longer than 24 hours (14).…”
Section: Introductionmentioning
confidence: 99%